Socioeconomic position and alcohol-related harm in Danish adolescents. Issue 9 (20th June 2019) - Møller, Sanne Pagh; Pisinger, Veronica Sofie Clara; Christensen, Anne Illemann; Tolstrup, Janne S
Abstract : Background: In adults, it has consistently been observed that with equal alcohol consumption levels, alcohol harms individuals with low socioeconomic position (SEP) more than individuals with high SEP. It is unknown if this so-called alcohol harm paradox is also present in adolescents. We aim to test the hypothesis that low SEP is associated with more alcohol-related harm as compared with higher SEP in Danish adolescents. Methods: We used survey data from the Danish National Youth Study 2014 including 70 566 students from 119 high schools. Alcohol-related harm was measured by self-report as having been in a fight, involved in an accident, had problems with parents or friends, had sex that was regretted afterwards and done drugs that was regretted afterwards, because of alcohol. Further, a combined measure was constructed defined as having experienced any harm more than once within the last year. SEP was measured as parents' educational level, family income, parents' employment status and experiencing financial strain in the family. Analyses were adjusted by age, sex, perceived ethnicity, class type and binge drinking. Results: Lower SEP was associated with higher odds of experiencing alcohol-related harm more than once as compared with highest SEP, and lower SEP was associated with higher odds of having been in a fight, problems with parents or friends, sex and regretting afterwards or drugs and regretting afterwards, as compared with highest SEP. These associations were statistically significant. Adjustment for the frequency of binge drinking did not change results. Conclusion: The alcohol harm paradox exists in Danish adolescents, and this should be addressed in future prevention strategies to reduce the risk of alcohol-related harm among adolescents.